2019
DOI: 10.3847/2041-8213/aafe82
|View full text |Cite
|
Sign up to set email alerts
|

Dynamo Wave Patterns inside of the Sun Revealed by Torsional Oscillations

Abstract: Torsional oscillations represent bands of fast and slow zonal flows around the Sun, which extend deep into the convection zone and migrate during solar cycles towards the equator following the sunspot butterfly diagram. Analysis of helioseismology data obtained in 1996-2018 for almost two solar cycles reveals zones of deceleration of the torsional oscillations inside the Sun due to dynamo-generated magnetic field. The zonal deceleration originates near the bottom of the convection zone at high latitudes, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 41 publications
7
21
0
Order By: Relevance
“…At lower latitudes, they propagate upward from the bottom of the convection zone, and form almost stationary oscillatory patterns in the subsurface layer, the depth of which increases with the latitude decrease. These effects qualitatively correspond to the results of our recent helioseismology analysis (Kosovichev & Pipin 2019). Snapshots for a half of the model M1 dynamo cycle of: a) the toroidal magnetic field (background image) and streamlines of the poloidal field (contours); b) variations of the zonal acceleration (background image) and the azimuthal force caused by variations of the meridional circulation, δFU , (contour lines are plotted in the range ±50 m/s 2 ); c) variations of the azimuthal velosity and contours show streamlines of the meridional circulation, dashed lines are for the counter clockwise circulation; d) the azimuthal force caused by the dynamo-induced Λ-effect, δF H (0,ρ) (density stratification, background image), δF H (0,a) (effect of anisotropy, contours are in the same range of magnitudes), see the Eqs (10) in the upper part of the convection zone and downward in the tachocline.…”
Section: Effect Of the Extended Dynamo Modesupporting
confidence: 91%
See 3 more Smart Citations
“…At lower latitudes, they propagate upward from the bottom of the convection zone, and form almost stationary oscillatory patterns in the subsurface layer, the depth of which increases with the latitude decrease. These effects qualitatively correspond to the results of our recent helioseismology analysis (Kosovichev & Pipin 2019). Snapshots for a half of the model M1 dynamo cycle of: a) the toroidal magnetic field (background image) and streamlines of the poloidal field (contours); b) variations of the zonal acceleration (background image) and the azimuthal force caused by variations of the meridional circulation, δFU , (contour lines are plotted in the range ±50 m/s 2 ); c) variations of the azimuthal velosity and contours show streamlines of the meridional circulation, dashed lines are for the counter clockwise circulation; d) the azimuthal force caused by the dynamo-induced Λ-effect, δF H (0,ρ) (density stratification, background image), δF H (0,a) (effect of anisotropy, contours are in the same range of magnitudes), see the Eqs (10) in the upper part of the convection zone and downward in the tachocline.…”
Section: Effect Of the Extended Dynamo Modesupporting
confidence: 91%
“…The robustness of our conclusions depends on the radial distribution of the large-scale field, which determines the zonal flow acceleration in the convection zone. Comparing results of our model with those from the recent paper by Kosovichev & Pipin (2019), (e.g., with their Figure 2) we see that in our models the latitudinal width of the zonal flow acceleration pattern is somewhat smaller than in the observations. At the mid latitudes, the models show the axially aligned zonal flow acceleration patterns.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Basu et al (2012) reported that low-degree helioseismic data indicated that Cycle 24 would be very different, and recently Howe et al (2017) have shown that the difference in characteristics has continued to date. An early examination of solar rotation during the minimum just before Cycle 24 (Antia & Basu 2010 has revealed that the solar rotation profile was different from that of the minimum before Cycle 23, and studies show that the differences have continued (see e.g., Howe et al 2013b;Komm et al 2014;Howe et al 2018;Kosovichev & Pipin 2019). We present the results of an independent helioseismic study sarbani.basu@yale.edu arXiv:1908.05282v1 [astro-ph.SR] 14 Aug 2019 of solar dynamics using both ground-based and space-based helioseismic data.…”
Section: Introductionmentioning
confidence: 94%